Expression and purification of horseradish peroxidase in insect larvae - Loustau, María N. (2008)
A strategy for obtaining a high-level expression of horseradish peroxidase isozyme C (HRPC) in insect larvae is herein described. The HRPC-6xHis coding sequence was inserted into the AcNPV genome via the pAcGP67HRPC-6xHis transfer vector to originate an AcHRPC-6xHis recombinant baculovirus of phenotype occ−. Rachiplusia nu larvae were injected with a viral stock derived from culture supernatants of Sf9 cells infected with AcHRPC-6xHis. Enzyme concentration at day 3 post-infection was 230 ± 10 mg/kg haemolymph and 100 ± 14 mg/kg larvae, an expression level never attained by other expression systems. HRPC-6xHis was purified from the crude larval extract or haemolymph by immobilised metal ion affinity chromatography with yields of 88.8% and 89.0% and purification factors of 18.9 and 14.0, respectively, in a single step. The purity of the final product was 90%.